x+2 | x−1 | x−1 | ||||
limx→∞( | ) | ( | jest w potędze) | |||
x−2 | 3 | 3 |
x+2 | 4 | |||
krok 1: | = (1 + | ) | ||
x−2 | x−2 |
4 | 1 | |||||||||
krok 2: (1 + | ) = (1 + | ) | ||||||||
x−2 |
|
x−1 | x−2 | 4 | x−1 | x−2 | 4x−4 | |||||||
krok 3: | = | * | * | = | * | |||||||
3 | 4 | x−2 | 3 | 4 | 3x−6 |
1 | ||
krok 4: stosujesz wzór: limf(x)−>∞ (1 + | )f(x) = e1 oraz ab*c = (ab)c | |
f(x) |
x − 2 + 4 | x−1 | 4 | x−1 | |||||
= lim( | ) | = lim [(1 + | )x−2]k i k = | |||||
x−2 | 3 | x−2 | 3(x−2) |
−1 | ||
oraz lim k = | ||
3 |
4 | ||
dzieki, chwila bo nie lapie skad sie wzielo 1+ | ![]() | |
x−2 |
x − 2 + 4 | x−2 | 4 | |||
= | + | ||||
x − 2 | x−2 | x−2 |
a + b | a | b | b | |||||
= | + | = 1 + | ||||||
a | a | a | a |
| 1 | ||||||||||||
= lim | = | ||||||||||||
| 3 |